Intelligent Automated System of Controlled Synthesis of MAO-Coatings - Golubkov, Pavel; Pecherskaya, Ekaterina; Karpanin, Oleg; Safronov, Maksim; Shepeleva, Juliya; Bibarsova, Aliya (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2019)
An intelligent automated system that allows the controlled synthesis of protective oxide coatings using micro-arc oxidation has been developed. The hardware and software structure and knowledge bank, the information exchange principles between the component parts of the device, as well as the software operation algorithm are given. The considered system allows to establish the relationship between the technological process parameters of the micro-arc oxidation and the properties of the formed coatings. This intelligent system can be used both for scientific research and for production in order to optimize the technological modes of micro-arc treatment.